The Role of PDE8 in T Cell Recruitment and Function in Inflammation - Epstein, Paul M.; Basole, Chaitali; Brocke, Stefan (Frontiers in Cell and Developmental Biology, 2021)
Inhibitors targeting cyclic nucleotide phosphodiesterases (PDEs) expressed in leukocytes have entered clinical practice to treat inflammatory disorders, with three PDE4 inhibitors currently in clinical use as therapeutics for psoriasis, psoriatic arthritis, atopic dermatitis and chronic obstructive pulmonary disease. In contrast, the PDE8 family that is upregulated in pro-inflammatory T cells is a largely unexplored therapeutic target. It was shown that PDE8A plays a major role in controlling T cell and breast cancer cell motility, including adhesion to endothelial cells under physiological shear stress and chemotaxis. This is a unique function of PDE8 not shared by PDE4, another cAMP specific PDE, employed, as noted, as an anti-inflammatory therapeutic. Additionally, a regulatory role was shown for the PDE8A - rapidly accelerated fibrosarcoma (Raf)-1 kinase signaling complex in myelin antigen reactive CD4+ effector T cell adhesion and locomotion by a mechanism differing from that of PDE4. The PDE8A-Raf-1 kinase signaling complex affects T cell motility, at least in part, via regulating the LFA-1 integrin mediated adhesion to ICAM-1. The findings that PDE8A and its isoforms are expressed at higher levels in naive and MOG35-55 activated effector T (Teff) cells compared to regulatory T (Treg) cells and that PDE8 inhibition specifically affects MOG35-55 activated Teff cell adhesion, indicates that PDE8A could represent a new beneficial target expressed in pathogenic Teff cells in CNS inflammation. The implications of this work for targeting PDE8 in inflammation will be discussed in this review.